Disclosure Deregulation of Quarterly Reporting - Vanessa Behrmann; Lars Hornuf; Jochen Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this article, we investigate the deregulation efforts resulting from the 2015 transposition of the EU's Transparency Directive into German law and analyze whether a reduction in the minimum content requirements for quarterly reporting increases information asymmetries and decreases firm value. Using a novel dataset of firms that are listed on the Frankfurt Stock Exchange, our results reveal that over the period from 2012 to 2019, lower quarterly reporting levels on average have increased information asymmetry and reduced firm value. We find that this effect is stronger for second-tier stocks and firms with low media coverage. Our results are robust to potential selection effects regarding firms' choice of quarterly reporting content levels.
Keywords: G14; G32; 330; quarterly reporting; disclosure deregulation; financial reporting; interim management statement; transparency directive